2018
DOI: 10.1080/01972243.2018.1497744
|View full text |Cite
|
Sign up to set email alerts
|

Moving on up in the information society? A longitudinal analysis of the relationship between Internet use and social class mobility in Britain

Abstract: Many universal access policies are based on the assumption that the removal of the digital divide will enhance social mobility. But this assumption is not supported by the available evidence and hence remains an open question. Using four waves of longitudinal data from Britain we show that Internet use has a positive effect on social class mobility, while controlling for age, gender, education, health, and previous social class membership between 1997 and 2013. In doing so, we contribute to a wider discussion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 62 publications
0
12
0
2
Order By: Relevance
“…En estos escenarios, las tasas de jóvenes, estudiantes, migrantes, trabajadores y habitantes que usan de manera intensiva la tecnología en sus labores suelen ser poco representados (Büchi et al, 2016;. A esto se le suma el rechazo de los proveedores de internet de suministrar el servicio en este tipo de localidades, la baja motivación de algunos residentes para contratar el servicio e inclusive el desarrollo de una actitud refractaria hacia las TIC, situaciones que pueden observarse como barreras significativas al considerar la disponibilidad de la red en los hogares (Eynon et al, 2018;Lindblom y Räsänen, 2017).…”
Section: Brecha Digital Y Disponibilidad De Internet En Casaunclassified
See 1 more Smart Citation
“…En estos escenarios, las tasas de jóvenes, estudiantes, migrantes, trabajadores y habitantes que usan de manera intensiva la tecnología en sus labores suelen ser poco representados (Büchi et al, 2016;. A esto se le suma el rechazo de los proveedores de internet de suministrar el servicio en este tipo de localidades, la baja motivación de algunos residentes para contratar el servicio e inclusive el desarrollo de una actitud refractaria hacia las TIC, situaciones que pueden observarse como barreras significativas al considerar la disponibilidad de la red en los hogares (Eynon et al, 2018;Lindblom y Räsänen, 2017).…”
Section: Brecha Digital Y Disponibilidad De Internet En Casaunclassified
“…Este objetivo de globalizar el acceso a la red fue elevado por una legitimidad adquirida gracias a la premura de la masificación de internet, servicio que condiciona el acceso a los beneficios de la "revolución digital" y su corolario: la sociedad de la información (Castells, 2002;Graham, 1998;Eynon et al, 2018). Independientemente de la pertinencia de los postulados sociotecnológicos asociados a las tecnologías de la información y la comunicación (TIC), para el discurso dominante en estos contextos, la disponibilidad de la web se ha vuelto un paso imprescindible para la integración social.…”
Section: Introductionunclassified
“…These studies unravel the emphasis that large-scale literacy measurements have placed upon decontextualised literacy tasks and upon individual autonomy (Lankshear and Knobel 2007;Hamilton 2016), a perspective that is important when considering the socio-materiality of literacies in digital contexts. Shepherd and Hearne (2019) observe that narrowly defining digital literacy skills in terms of problem-solving tasks neglects the full range and complexities of online practices and the ways in which digital and automated technologies can intensify rather than even out inequalities (Eubanks 2018, Eynon et al 2018, Noble 2018, Smythe 2018. For example, few studies concerned with technology skills and employability consider that consistent digital access (including affordable and secure Internet, a computer, printer, phone, and so on) is required to apply for, let alone, secure and maintain employment.…”
Section: Framing Literaturementioning
confidence: 99%
“…In recent years, more scholars have tested the role of internet use in social stratification and social mobility based on empirical research design. Eynon et al based on the analysis of four waves of longitudinal data from the United Kingdom, found that internet use helps to improve social mobility, and this effect is more significant in western developed countries and the promotion of social stratification represented by occupational status [ 40 ]. Kappeler et al took how the digital divide in Switzerland—social differences in Internet adoption—evolved from 2011 to 2019 as an example, and found that the use of the Internet was still stratified according to existing social stratifications, while the situation of not using the Internet was increasingly concentrated in traditionally disadvantaged occupations [ 41 ].…”
Section: Introductionmentioning
confidence: 99%